Kinetics and efficacy of an organophosphorus hydrolase in a rodent model of methyl-parathion poisoning - Gresham, Chip (2010)
OBJECTIVES: Organophosphorus (OP) pesticides exert a tremendous health burden, particularly in the developing world. Limited resources, the severity of intentional OP ingestions, and a paucity of beneficial therapies all contribute to the morbidity and mortality of this broad class of chemicals. A novel theoretical treatment for OP poisoning is the use of an enzyme to degrade the parent OP in the circulation after poisoning. The aims of this study were to determine the pharmacokinetics and efficacy of an OP hydrolase (OpdA) in a rodent model of severe methyl-parathion poisoning. METHODS: Two animal models were used. First, Wistar rats were administered two different doses of the hydrolase (0.15 mg/kg and 1.5 mg/kg), and the ex vivo hydrolytic activity of plasma was determined by a fluorometric method. Second, an oral methyl-parathion animal poisoning model was developed to mimic severe human poisoning, and the efficacy of post-poisoning OpdA (as measured by survival to 4 hours and 24 hours) was determined. RESULTS: The half-life of OpdA in the Wistar rat was dependent upon the dose administered, and ranged between 45.0 and 57.9 minutes. The poisoning model of three times the lethal dose to 50% of the population (3×LD(50)) of methyl-parathion resulted in 88% lethality at 4 and 24 hours. Using a single dose of 0.15 mg/kg OpdA 10 minutes after poisoning resulted in 100% survival at 4 hours (p = 0.001 vs. placebo), but 0% at 24 hours post-poisoning (p = NS vs. placebo). CONCLUSIONS: The OP hydrolase OpdA exhibits pharmacokinetics suitable for repeated dosing and increases short-term survival after severe methyl-parathion poisoning.